Alemtuzumab depletion failure can occur in multiple sclerosis. Issue 2 (4th January 2018) - Dubuisson, Nicolas; Baker, David; Kang, Angray S.; Pryce, Gareth; Marta, Monica; Visser, Leo H.; Hofmann, Werner E.; Gnanapavan, Sharmilee; Giovannoni, Gavin; Schmierer, Klaus
Summary: Alemtuzumab is a lymphocyte‐depleting antibody and one of the most effective treatments for relapsing multiple sclerosis. However, it also causes loss of immune‐tolerance leading to secondary autoimmunity and marked anti‐drug antibody responses. Although these anti‐drug responses have been reported to be of no significance, we hypothesized that they will affect the depleting capacity and treatment response in some individuals. This was found following analysis of the regulatory submission of the pivotal phase III trials, which was obtained from the European Medicines Agency. At the population level there was lack of influence of 'ever‐positive' alemtuzumab‐specific antibody responses on lymphocyte depletion, clinical efficacy and adverse effects during the 2‐year trial. This was not surprising as no one before the first infusion, and only 0·6% of people before the second‐infusion, had pre‐infusion, neutralizing antibodies (NAbs). However, at the individual level, NAbs led to poor lymphocyte depletion. Importantly, it was evident that 31% of people had NAbs and 75% had binding antibodies at the end of treatment‐cycle 2, which suggests that problems may occur in people requiring additional alemtuzumab cycles. In addition, we also identified individuals, following 'post‐marketing' alemtuzumab use, whose lymphocyte level was never effectively depleted after the first infusion cycle. Hence, although alemtuzumab depletes lymphocytes in most individuals, some people fail to deplete/deplete poorly, probably due to biological‐response variation and NAbs, and this may lead to treatment failure. Monitoring depletion following infusion and assessment of the neutralizing response before re‐infusion may help inform the decision to retreat or switch therapy to limit treatment failure. Abstract : Alemtuzumab is a CD52 + lymphocyte‐depleting humanized monoclonal antibody, although some people do not deplete on first infusion, indicating a resistance to treatment. Furthermore, although humanized, it rapidly induces a marked drug‐binding and drug‐neutralizing antibody response in most people. These limit depletion by the antibody in some individuals.